Treatment of Pediatric Septic Shock With the Surviving Sepsis Campaign Guidelines and PICU Patient Outcomes*. Issue 10 (October 2016) - Workman, Jennifer K.; Ames, Stefanie G.; Reeder, Ron W.; Korgenski, E. Kent; Masotti, Susan M.; Bratton, Susan L.; Larsen, Gitte Y.
Abstract : Objectives: The Surviving Sepsis Campaign recommends rapid recognition and treatment of severe sepsis and septic shock. Few reports have evaluated the impact of these recommendations in pediatrics. We sought to determine if outcomes in patients who received initial care compliant with the Surviving Sepsis Campaign time goals differed from those treated more slowly. Design: Single center retrospective cohort study. Setting: Emergency department and PICU at an academic children's hospital. Patients: Three hundred twenty-one patients treated for septic shock in the emergency department and admitted directly to the PICU. Interventions: None. Measurements and Main Results: The exposure was receipt of emergency department care compliant with the Surviving Sepsis Campaign recommendations (delivery of IV fluids, IV antibiotics, and vasoactive infusions within 1 hr of shock recognition). The primary outcome was development of new or progressive multiple organ dysfunction syndrome. Secondary outcomes included mortality, need for mechanical ventilation or vasoactive medications, and hospital and PICU length of stay. Of the 321 children studied, 117 received Surviving Sepsis Campaign compliant care in the emergency department and 204 did not. New or progressive multiple organ dysfunction syndrome developed in nine of the patients (7.7%) who received Surviving Sepsis Campaign compliant care and 25 (12.3%) who did not ( p = 0.26). There were 17 deaths; overall mortality rate was 5%. There were no significant differences between groups in any of the secondary outcomes. Although only 36% of patients met the Surviving Sepsis Campaign guideline recommendation of bundled care within 1 hour of shock recognition, 75% of patients received the recommended interventions in less than 3 hours. Conclusions: Treatment for pediatric septic shock in compliance with the Surviving Sepsis Campaign recommendations was not associated with better outcomes compared with children whose initial therapies in the emergency department were administered more slowly. However, all patients were treated rapidly and we report low morbidity and mortality. This underscores the importance of rapid recognition and treatment of septic shock. Abstract : Supplemental Digital Content is available in the text.